2021
DOI: 10.1371/journal.pone.0252322
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sonication cultures when the diagnosis of prosthetic joint infection is inconclusive

Abstract: Background In the absence of a gold standard criterion for diagnosing prosthetic joint infections (PJI), sonication of the removed implant may provide superior microbiological identification to synovial fluid and peri-implant tissue cultures. The aim of this retrospective study was to assess the role of sonication culture compared to tissue cultures for diagnosing PJI, using different consensus and international guidelines for PJI definition. Methods Data of 146 patients undergoing removal of hip or knee art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…Однако специфичность метода соникации сопоставима со стандартным микробиологическим исследованием: 90% и 100% соответственно [69]. При объединении методов соникации и микробиологического исследования показатель чувствительности составил 96,3% [70].…”
Section: соникацияunclassified
“…Однако специфичность метода соникации сопоставима со стандартным микробиологическим исследованием: 90% и 100% соответственно [69]. При объединении методов соникации и микробиологического исследования показатель чувствительности составил 96,3% [70].…”
Section: соникацияunclassified
“…The sonication of the liquid culture appears to improve the microbiological yield in orthopedic device-related infections. 8,9 Likewise, the treatment of orthopedic infections is also troublesome and difficult to standardize in clinical practice since systemic antimicrobials reach insufficient tissue bone concentrations and in the inner parts of the biofilm. To overcome this limitation, intraoperative administration of antibiotics has the potential to provide remarkably high local concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they identified the etiology of infections in 78.5% of cultures, compared to 60.8% of peri‐implant tissue cultures. The sonication of the liquid culture appears to improve the microbiological yield in orthopedic device‐related infections 8,9 . Likewise, the treatment of orthopedic infections is also troublesome and difficult to standardize in clinical practice since systemic antimicrobials reach insufficient tissue bone concentrations and in the inner parts of the biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, bacteria isolation and identification for diagnosing PJI is performed by means of cultures of synovial fluid and intraoperative periprosthetic tissues; however, diagnosis often fails due to the low sensitivity of this method 25 (about 60%). 26,27 This fact could be due to the protection that the biofilm offers to the pathogens with respect to detection and elimination. 28 In this context, some studies have shown that the sonication of removed implants and the culture of the sonication fluid culture shows a higher sensitivity (about 90%), 26,27 improving the diagnosis of PJI.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 This fact could be due to the protection that the biofilm offers to the pathogens with respect to detection and elimination. 28 In this context, some studies have shown that the sonication of removed implants and the culture of the sonication fluid culture shows a higher sensitivity (about 90%), 26,27 improving the diagnosis of PJI. The sonication technique relies on two effects of the ultrasound: cavitation and microstreaming.…”
Section: Introductionmentioning
confidence: 99%